2014
DOI: 10.1007/s00234-014-1466-4
|View full text |Cite
|
Sign up to set email alerts
|

Automatic segmentation and volumetric quantification of white matter hyperintensities on fluid-attenuated inversion recovery images using the extreme value distribution

Abstract: The proposed EVD-based segmentation framework is a promising, effective, and convenient tool for volumetric quantification and further study of WMHs in aging and dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…Intensity inhomogeneity correction was reported in 17/37 studies, and it was always performed using a well-known tool: N3 (or N4), SPM, FSL-FAST or the Nu estimate. N3 and its newer version N4, were the tools most commonly used for intensity inhomogeneity correction (Stone et al, 2016;Bowles, et al, 2017;Dadar et al, 2017a;Van Opbroek, Ikram, Vernooij & de Bruijne, 2015a, 2015bDamangir et al, 2017;Roy et al, 2015;Wang et al, 2015;Zhan et al, 2015;Zhan et al, 2017;Atlason et al, 2019;Ding et al, 2020). Non-local means was the only filtering technique used by the two studies that reported having included noise removal within their preprocessing steps (Manjón et al, 2018;Dadar et al, 2017a).…”
Section: Pre-processing Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Intensity inhomogeneity correction was reported in 17/37 studies, and it was always performed using a well-known tool: N3 (or N4), SPM, FSL-FAST or the Nu estimate. N3 and its newer version N4, were the tools most commonly used for intensity inhomogeneity correction (Stone et al, 2016;Bowles, et al, 2017;Dadar et al, 2017a;Van Opbroek, Ikram, Vernooij & de Bruijne, 2015a, 2015bDamangir et al, 2017;Roy et al, 2015;Wang et al, 2015;Zhan et al, 2015;Zhan et al, 2017;Atlason et al, 2019;Ding et al, 2020). Non-local means was the only filtering technique used by the two studies that reported having included noise removal within their preprocessing steps (Manjón et al, 2018;Dadar et al, 2017a).…”
Section: Pre-processing Methodsmentioning
confidence: 99%
“…Computing and Computer Assisted Intervention (MICCAI) segmentation challenges (Roy et al, 2015;Sudre et al, 2015;Van Obproek et al, 2015a, 2015bWang et al, 2015;Valverde et al, 2017;Zhan et al, 2017;Knight et al, 2018;Li et al, 2018;Manjón et al, 2018;Moeskops et al, 2018;Sundaresan et al, 2019;Wu, Zhang, Wang & Tang, 2019;Liu et al, 2020). Nine of them also used additional datasets or patient data from clinics.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…of the proposed methods use registration, brain extraction, bias field correction, and segmentation tools available in freely available toolkits; these include the SPM 8 toolkit[96,101,104,111,114,119,118,125,135] and the FSL 9 toolkit[64,99,106,116,117,124,125,133,137], as well as bias correction…”
mentioning
confidence: 99%